HIV Disease Progression to CD4 Count <200 Cells/μL and Death in Saskatoon, Saskatchewan - Stephanie Konrad; Stuart Skinner; Germain Bukassa Kazadi; Kali Gartner; Hyun June Lim (Canadian Journal of Infectious Diseases and Medical Microbiology)
OBJECTIVE: To characterize and identify determinants of HIV disease progression among a predominantly injection drug use (IDU) HIV population in the highly active antiretroviral therapy era.